HIV-1 incidence among people seeking voluntary counseling and testing centers, including pregnant women, in Pernambuco State, Northeast Brazil - Kledoaldo Oliveira de Lima; Daniela Medeiros Salustiano; Ana Maria Salustiano Cavalcanti; Élcio de Souza Leal; Heloísa Ramos Lacerda (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
The HIV-1 epidemic in Brazil has displayed new characteristics over time, with an increase in heterosexual transmission and a decline in the male-to-female ratio in AIDS cases. HIV screening was offered to patients attending the Voluntary Counseling and Testing Center in Paulista, Greater Metropolitan Recife, Pernambuco State, in Northeast Brazil, to determine HIV-1 incidence. BED capture enzyme immunoassay (BED-CEIA) was used to measure HIV-1 incidence, comparing it to the AxSYM avidity index method (Ax-AI). From 2006 to 2009, 14,014 individuals were tested, and only 18 pregnant women were diagnosed with HIV infection, resulting in 0.15% annual incidence (95%CI: 0-0.33), significantly lower than in men (1.03; 95%CI: 0.45-1.61) and non-pregnant women (0.50; 95%CI: 0.11-0.89). Despite the low HIV-1 incidence in pregnant women, the high rate of recent infection detected during prenatal care emphasizes the need to increase measures to prevent vertical transmission.